Networks and New Services: A Complete Story - Minerva, Roberto; Crespi, Noel.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book shines a spotlight on software-centric networks and their emerging service environments. The authors examine the road ahead for connectivity, for both humans and 'things', considering the rapid changes that have shaken the industry. The book analyses major catalytic shifts that are shaping the communications world: softwarization, virtualization, and cloud computing. It guides the reader through a maze of possible architectural choices, driven by discriminating and sometimes conflicting business considerations. The new ICT capabilities lead us toward smarter environments and to an ecosystem where applications are backed up by shared networking facilities, instead of networks that support their own applications. Growing user awareness is a key driver towards the softwarization process. Softwarization disrupts the current status quo for equipment, development, networks, operations and business. It changes radically the value chain and the involved stakeholders.The dilemma is between a 'slow burn' traditional step-by-step approach and a bold transformation of the whole infrastructure and business models.  This book is essential reading for those seeking to build user-centric communication networks that support independent agile and smart applications. "The book gives an insightful account of modern telecom networks, pinpointing the radical transformations of the last 20 years. This is the perfect read for those who are interested in the grand challenges of networks and in the socio-economic reasons why the telecom industry to embrace the Internet of Things and cyber-physical systems." Prof. Antonio Liotta, Eindhoven University of Technology "This book fulfills an urgent need to thoroughly analyze the entanglement of network and software architectures by taking into account the increasing softwarization. It highlights important issues behind today's business models and opens the road for sustainable future approaches to provide user appreciated valuable services." Dr. Eng. Hendrik Berndt, former CTO of NTT DOCOMO Communications Laboratories Europe.
Chapter 1. Introduction -- Chapter 2. Background: Services, Control Paradigms, and Network Architectures -- Chapter 3. Technological Evolution of the ICT Sector -- Chapter 4. The New Networks -- Chapter 5. Emerging Service and Applications Scenarios -- Chapter 6. How the TelCos Sustain their Connectivity based Business Model in the Wave of Disruption Generated by the Technological Evolution.
Keywords: Computer networks .; Telecommunication; Computer Communication Networks; Communications Engineering, Networks